"Like filling a lottery ticket with quite high stakes": a qualitative study exploring mothers' needs and perceptions of state-provided financial support for a child with a long-term illness in Finland - Anna Paajanen; Kristi Sidney Annerstedt; Salla Atkins (BMC, 2021)
Abstract Background A child's long-term illness or disability is always a serious matter that impacts the whole family. Costs related to an illness can substantially affect a family's financial situation. To date, there is little research on how parents experience available support for financial assistance. Surveys in Finland have found that families of children with long-term illnesses and disabilities could experience financial struggle and perceive the state provided financial support system as too complex. This article aimed to explore how caregivers of children with long-term illnesses perceived their financial situation, need for financial support and experienced its provision by the state in the Helsinki greater region. Methods Convenience sampling was used. Participants were contacted through peer-support groups on Facebook. Eleven mothers of children with varying long-term illnesses and disabilities residing in the Helsinki greater region were interviewed using in-depth interviews. Recordings of the interviews were transcribed and analysed using framework analysis. An analytical framework was built to label the dataset, which was then charted. Lastly, themes were formed through descriptive analysis. Results The main findings showed how the burden of caring for a child with a long-term illness or disability causes fatigue, which affects a family's financial situation holistically. This affected both employment and financial management, but also receiving information about and applying for the state provided allowances. Mental resources were further depleted by seeking information and applying for allowances. This contributed to a vicious cycle between parental fatigue and financial struggle. Participants found the allocation of funds inequitable across the country. Finally, participants thought the allowance was insufficient in compensating for time spent caring for their child's illness and did not consider their mental strain. Conclusions Even in a welfare state such as Finland, caregivers of children with long-term illnesses are at risk of poverty and struggle with the organization of state provided financial support. Policies should be designed to ensure equity across the country and consider how the parental fatigue should be addressed. The study has implications for achieving sustainable development goals on wellbeing and reducing poverty.